2003
DOI: 10.4049/jimmunol.170.3.1466
|View full text |Cite
|
Sign up to set email alerts
|

The Long Pentraxin Ptx3 Is Synthesized in IgA Glomerulonephritis and Activates Mesangial Cells

Abstract: The long pentraxin PTX3 has been recently involved in amplification of the inflammatory reactions and regulation of innate immunity. In the present study we evaluated the expression and role of PTX3 in glomerular inflammation. PTX3 expression was investigated in the IgA, type I membranoproliferative, and diffuse proliferative lupus glomerulonephritis, which are characterized by inflammatory and proliferative lesions mainly driven by resident mesangial cells, and in the membranous glomerulonephritis and the foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 35 publications
2
58
0
Order By: Relevance
“…It has been reported that renal mesangial and epithelial cells produce PTX3 (61,62). It is possible to hypothesize that a mechanism involving a disturbed interaction of locally produced PTX3 with FH could be involved in the pathogenesis of this condition.…”
Section: ϫ7mentioning
confidence: 99%
“…It has been reported that renal mesangial and epithelial cells produce PTX3 (61,62). It is possible to hypothesize that a mechanism involving a disturbed interaction of locally produced PTX3 with FH could be involved in the pathogenesis of this condition.…”
Section: ϫ7mentioning
confidence: 99%
“…For example, renal cells produce pentraxin-3, which has the potential to directly inhibit leukocyte recruitment by interfering with P-selectin on the surface of activated endothelial cells. 68,69 In lupuslike autoimmunity of C57BL/6 lpr/lpr mice, the role of pentraxin-3 seems to be organ specific, because it suppresses lymphocyte recruitment to the lungs but not to the kidney. 70 Infiltrating leukocytes form de novo perivascular tertiary lymphoid organs inside the kidney, which involve the clonal expansion and ongoing somatic hypermutation of B cells in proximity to T cell aggregates.…”
Section: Intrarenal Pathogenic Mechanisms Of Lnmentioning
confidence: 99%
“…The production of PTX3 in human renal epithelial cells was recently reported (22), together with an increased PTX3 expression in mesangial cells of renal biopsies obtained from patients with IgA glomerulonephritis (23), suggesting a role in the innate immune response and inflammatory reactions in the kidney. The bigger molecular size for PTX3 (40.6 kD) compared with CRP (21.5 kD) may suggest increased retention in uremia.…”
mentioning
confidence: 99%